(untitled) (Journal of the College of Basic Education, 2023)
The research is a serious and modest attempt to show the primacy of Islamic law and the delay of man-made laws inall fields; Including the field of veterinary work, which deals with all kinds of livestock, and perhaps the words of AmirThe faithful Ali Ibn Abi Talib (may God be pleased with him)Guarantor) an explicit guide that came specific to all profession controls. The research showed that the farrier is not responsible for the results if he practices his profession according to the controls drawn up for thisPort Aita, therefore, otherwise, by intentionally causing harm or making an obscene mistake, take full responsibility. The researcher stressed the need for the state to adopt the profession to advance its reality from all sidesExpanding the involvement of veterinary students in scientific courses in universities and laboratories around the world for their development